Approaching a National Film History through Data. Network Analysis in German Film History - Malte Hagener; Theresa Blaschke (Journal of Cultural Analytics)
The present paper is an attempt at importing network analysis as a method and applying it to a field that has hitherto been examined in different ways: the study of national cinema. The approach was motivated by the perceived conundrum in the existing studies of German cinema that filmhistorical and political history usually do not match. The aim is to open up another perspective on the problem of periodization by looking at the data of film production, more specifically of collaboration. By using a comprehensive data set which is made availavable by the Filmportal, the central internet platform on German film, the approach in this paper is to look at the key creatives involved in the production of a film in the period from 1919 to 1939 and to conceptualize collaboration and connectivity in a (national) film culture through the use of network research methods.